Does the Home Bias Explain Missing Trade in Factors? - Robert Stehrer (The Vienna Institute for International Economic Studies (wiiw), 2014)
Abstract It is now widely accepted that when controlling for international differences in production techniques, the predictions from the Heckscher-Ohlin-Vanek (HOV) theorem are largely satisfied. However, a large amount of 'missing trade' remains. This paper makes two main contributions Firstly, the HOV is tested for various production factors including labour by educational attainment levels (high, medium, low) and capital. Secondly, the paper allows for a more general structure of final consumption in the HOV framework with technology differences, which reduces the amount of missing trade. We test for the effects of non-homothetic preferences, home bias of consumption and the role of distance at the country and industry level. We discuss how this can be tackled in the analytical framework both for a country's total exports but also in a bilateral way. Results are shown both for total trade and bilateral trade. Empirically we draw on the recently released World Input-Output Database (WIOD) and show the extent of reductions in 'missing trade' caused by the various assumptions and restrictions on demand structures.
Keywords: F1; F15; F19; 330; factor content of trade; Heckscher-Ohlin-Vanek; home bias; non-homothetic tastes; technology